The formation of the is professional-creative orientation of students of technical specialities - A M Romanova (Peoples' Friendship University of Russia (RUDN University), 2010)
This article is dedicated to the problem of creating engineers personality through the processes of developing profession-artistic directivity of students of technological universities. Collection of pedagogical conditions necessary to maintain the process of developing profession-creative directivity of students of technological universities while studying foreign language.